Once upon a time there was a consumer…: stories of magic and the magic of stories - Heath, Teresa; Heath, Matthew (Taylor and Francis, 2016)
This paper explores how the centrality of narrative to people’s understandings of the world, and the power of stories of enchantment in particular, colour consumer culture. Specifically, it analyses the ways in which fantastic themes of magic and heroism are used in the discourses of marketing scholars and practitioners, as well as consumers to shape views of consumption and marketing. It further illuminates the role that marketers and consumers each have in imbuing consumption with a sense of enchantment and situates this phenomenon within the dominant neoliberal ideology. Finally, it discusses implications for marketing theory and for practices aimed at reducing excessive consumption related to such enchantment.